Low nuclear body formation and tax SUMOylation do not prevent NF-kappaB promoter activation - Bonnet, Amandine (BioMed Central, 2012)
BACKGROUND: The Tax protein encoded by Human T-lymphotropic virus type 1 (HTLV-1) is a powerful activator of the NF-κB pathway, a property critical for HTLV-1-induced immortalization of CD4(+) T lymphocytes. Tax permanently stimulates this pathway at a cytoplasmic level by activating the IκB kinase (IKK) complex and at a nuclear level by enhancing the binding of the NF-κB factor RelA to its cognate promoters and by forming nuclear bodies, believed to represent transcriptionally active structures. In previous studies, we reported that Tax ubiquitination and SUMOylation play a critical role in Tax localization and NF-κB activation. Indeed, analysis of lysine Tax mutants fused or not to ubiquitin or SUMO led us to propose a two-step model in which Tax ubiquitination first intervenes to activate IKK while Tax SUMOylation is subsequently required for promoter activation within Tax nuclear bodies. However, recent studies showing that ubiquitin or SUMO can modulate Tax activities in either the nucleus or the cytoplasm and that SUMOylated Tax can serve as substrate for ubiquitination suggested that Tax ubiquitination and SUMOylation may mediate redundant rather than successive functions. RESULTS: In this study, we analyzed the properties of a new Tax mutant that is properly ubiquitinated, but defective for both nuclear body formation and SUMOylation. We report that reducing Tax SUMOylation and nuclear body formation do not alter the ability of Tax to activate IKK, induce RelA nuclear translocation, and trigger gene expression from a NF-κB promoter. Importantly, potent NF-κB promoter activation by Tax despite low SUMOylation and nuclear body formation is also observed in T cells, including CD4(+) primary T lymphocytes. Moreover, we show that Tax nuclear bodies are hardly observed in HTLV-1-infected T cells. Finally, we provide direct evidence that the degree of NF-κB activation by Tax correlates with the level of Tax ubiquitination, but not SUMOylation. CONCLUSIONS: These data reveal that the formation of Tax nuclear bodies, previously associated to transcriptional activities in Tax-transfected cells, is dispensable for NF-κB promoter activation, notably in CD4(+) T cells. They also provide the first evidence that Tax SUMOylation is not a key determinant for Tax-induced NF-κB activation.